EXPLORATION AND IDENTIFICATION OF ARBUSCULAR MYCORRHIZAL FUNGI FROM THE RHIZOSPHERE OF CHILI PLANTS (Capsicum Annuum L) IN BOGOR - ., Munarti; Wulan, Annisa; Utami, Agus (Journal of Science Innovare, 2018)
Mycorrhiza is ana structural and functional association between specific fungus and the roots of symbiotic relationship between mutualisme functions with a high degree of plant roots. Benefits of mycorrhiza for plant growth and development as its host is to increase the absorption of nutrient elements of soils, as biological barrier against infection of root pathogen, enhancing the resilience of crops to drought and increasing hormone boosters grows. This research aims to identify a arbuskular mycorrhiza fungi isolated from chilli plants rhizosphere in the village of Cilubang Mekar, Gunung Picung, Cikoneng, dan Kampung Baru. The results of this research show that the exploration and characterization of spores that develop on the roots of chilli in the village indicates a growing spores there is the genus Acaulopora, Gigaspora, andGlomus.type of Spore that successfully identified a species of Glomus sp 1, Glomus sp 2, Glomus sp 3.